Analgesic effect of intravesical lignocaine in urology surgery: A systematic review and meta-analysis - Ka T. Ng; Wei E. Lim; Wan Y. Teoh; Ahmad N. B. Fadzli; Mohd F. B. Z. Abidin (Indian Journal of Anaesthesia)
Background and Aims: Recent trials showed that transurethral lignocaine for bladder irrigation provides excellent analgesic effects and can minimise catheter-related bladder discomfort. The primary objective was to determine the efficacy of intravesical lignocaine on the incidence of catheter-related bladder discomfort in adult patients undergoing urologic surgery. Methods: The MEDLINE, EMBASE, and CENTRAL databases were searched from their start date until December 2024. Randomised clinical trials (RCTs) were included, comparing intravesical lignocaine and control for bladder irrigation in adults undergoing urological surgery. The odds ratio (OR) of the incidence of severe, moderate, and mild catheter-related bladder discomfort and the incidence of rescue analgesia were assessed. The revised Cochrane risk-of-bias tool for RCTs was applied to evaluate the risk of bias in all included studies. GRADEpro was used to evaluate the quality of the evidence. Results: Compared to the control group, our pooled analysis of three RCTs showed that intravesical lignocaine significantly reduced the incidence of severe catheter-related bladder discomfort (OR: 0.27, 95% confidence interval (Cl): 0.12, 0.58, P = 0.0008, grade of evidence: low) and the incidence of moderate catheter-related bladder discomfort (OR: 0.31, 95% Cl: 0.14, 0.67, P = 0.003, grade of evidence: low). It also statistically decreased the incidence of rescue analgesia (OR: 0.06, 95% Cl: 0.02, 0.15, P < 0.00001, grade of evidence: low). Conclusions: The intravesical administration of lignocaine statistically reduced moderate and severe catheter-related bladder discomfort. There was a significant decrease in the number of patients requiring rescue analgesia in the intravesical lignocaine group.